The composition of gaseous products of low-temperature oxidation of coal mass and biomass depending on temperature. (September 2016) - Derychova, Katerina; Perdochova, Michaela; Veznikova, Hana; Bernatik, Ales
Abstract: Coal and biomass emit gases during storage. The composition and quantity of these gases is dependent on many factors. This study deals with gaseous products that are released during coal and sawdust heating to find how the composition of gaseous products varies in dependence on temperature changes and how these changes can be used to indicate the condition of the stored materials. Samples were examined in a furnace, being placed in a cube-shaped basket whose side measured 5 cm. The samples were heated in the temperature range of 50–200 °C with increments of 50 °C for 180 min. Qualitative and quantitative analysis of the generated gases was performed using a FTIR spectrometer and a gas analyzer. The analysis indicated that these gaseous products primarily contain water vapour, carbon oxides and aliphatic hydrocarbons. At 200 °C, methanol appeared in the gaseous products released by the wood material. The measured results show that the amount of CO2, CO and CH4 increases with heating temperature. It has also been found that the CO/CO2 ratio is temperature - dependent in coal while this dependence is not so clear for sawdust. The results are useful for assessing the impact of temperature on the amount of gaseous products polluting the working and living environment and can help in selecting appropriate security measures. Highlights: Evolution of gaseous products of low-temperature oxidation of coal and biomass at various temperatures. Water, carbon oxides and aliphatic hydrocarbons release from heating of coal and wood sawdust. Methanol releases from heating wood sawdust at 200 °C. Volume of CO, CO2, CH4 increase with increase of temperature, amount of gases is higher for coal than for wood. CO/CO2 ratio is more dependent on temperature by coal than sawdust.